Historical and methodological highlights of quarantine measures: from ancient plague epidemics to current coronavirus disease (COVID-19) pandemic - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2020)
The ongoing 2020 coronavirus disease (COVID-19) pandemic is an enormous challenge for the health systems and the entire societies of the countries involved. Since at present the outbreak continues to evolve (April 2020), the World Health Organization (WHO) has declared it a public health emergency of international concern, specifying that public health interventions aimed at the prevention of the further spread of this disease include quarantine. Quarantine, that may be defined as a restraint on the activities of people or on the traffic of goods, targeted to the prevention of the diffusion of communicable pathologies, is a health concept profoundly rooted in the history of mankind.The lessons of the past are always pertinent for the present and for the future, in particular from a public health standpoint. One of the most relevant of them is connected with previous influenza pandemics, similar to the current COVID-19 2019/2020 pandemic, and it indicates that it is practically impossible, even in recent times, to contain the infection in the geographic area where it has risen and to prevent its trans-national disseminated spread. With specific reference to the COVID-19 pandemic, therefore, health authorities still adopt "classical" preventive interventions, namely workplace social distancing measures and quarantine, to reduce the transmission of the disease. Only the future will testify the precise overall effectiveness of preventive public health measures in containing the impact of the present coronavirus pandemic. However, what in this epidemiological scenario is already known, is that the multi-century international health value of quarantine remains essential and unavoidable.